2023
DOI: 10.1021/acs.inorgchem.2c04261
|View full text |Cite
|
Sign up to set email alerts
|

Ce-Modified Flowerlike NiFe-MOF Nanostructure Based on Ion Competitive Coordination for Enhancing the Oxygen Evolution Reaction

Abstract: Metal−organic framework (MOF) has become a popular electrocatalyst for the oxygen evolution reaction (OER) because of its large specific surface area and adjustable porosity. Nevertheless, the electrochemical performance of MOFs has been greatly limited by poor intrinsic conductivity and catalytic activity. Herein, we report a Ce-doped nanoflower-like MOF material Ce@ NiFe-MOF-5 via a facile ion competitive coordination effect and doping method. Benefiting from the nanoflower structure formed by the stacking o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Dalton Therefore, the introduction of the Ce element can effectively reduce charge-transport impedance and improve the electron transfer rate, thereby promoting electrocatalytic kinetics. As reported in previous literature, [67][68][69][70][71] rare earth elements can effectively modulate the electronic structures and reduce the H* absorption energy, further promoting HER activity. In a word, the above comparative results of the EIS test further demonstrated the importance and effectiveness of the 3d-4f mixed metal strategy.…”
Section: Papermentioning
confidence: 56%
See 1 more Smart Citation
“…Dalton Therefore, the introduction of the Ce element can effectively reduce charge-transport impedance and improve the electron transfer rate, thereby promoting electrocatalytic kinetics. As reported in previous literature, [67][68][69][70][71] rare earth elements can effectively modulate the electronic structures and reduce the H* absorption energy, further promoting HER activity. In a word, the above comparative results of the EIS test further demonstrated the importance and effectiveness of the 3d-4f mixed metal strategy.…”
Section: Papermentioning
confidence: 56%
“…74,75 The percentage of Ce 4+ decreases after the test, which may be due to the reduction of Ce 4+ to Ce 3+ during the OER. 71 More discussion about XPS results for initial FeMn 6 Ce 0.5 -MOF-74/NF can be found in the ESI. † The above comparison of XPS further proves the change of electronic states in FeMn 6 Ce 0.5 -MOF-74/NF electrode materials during the electrochemical test.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…When the current density was 10 mA cm −2 , the overpotential of this material was as low as 254 mV; 28 Wei's team doped Ce ions into flowerlike NiFe-MOF nanostructure, showing an oxygen evolution overpotential of 258 mV at 10 mA cm −2 and a Tafel slope of 54.44 mV dec −1 . 29 Significantly, previous researches found that the partial replacement of Fe 3+ by Ce 3+ or La 3+ affected the electronic structure of CoFe LDH, which could reduce the crystallite size and enhance the electronic coordination in the system. 30,31 Usually, powdered OER catalysts need to be coated on the electrode with a polymer binder, which hinders the utilization of pore volume, porosity of catalysts, and reachability of the active sites.…”
Section: Introductionmentioning
confidence: 97%